A comprehensive analysis of the response of the fungal community structure to long-term continuous cropping in three typical upland crops - Hang LIU; Feng-juan PAN; Xiao-zeng HAN; Feng-bin SONG; Zhi-ming ZHANG; Jun YAN; Yan-li XU (Journal of Integrative Agriculture)
Certain agricultural management practices are known to affect the soil microbial community structure; however, knowledge of the response of the fungal community structure to the long-term continuous cropping and rotation of soybean, maize and wheat in the same agroecosystem is limited. We assessed the fungal abundance, composition and diversity among soybean rotation, maize rotation and wheat rotation systems and among long-term continuous cropping systems of soybean, maize and wheat as the effect of crop types on fungal community structure. We compared these fungal parameters of same crop between long-term crop rotation and continuous cropping systems as the effect of cropping systems on fungal community structure. The fungal abundance and composition were measured by quantitative real-time PCR and Illumina MiSeq sequencing. The results revealed that long-term continuous soybean cropping increased the soil fungal abundance compared with soybean rotation, and the fungal abundance was decreased in long-term continuous maize cropping compared with maize rotation. The long-term continuous soybean cropping also exhibited increased soil fungal diversity. The variation in the fungal community structure among the three crops was greater than that between long-term continuous cropping and rotation cropping. Mortierella, Guehomyces and Alternaria were the most important contributors to the dissimilarity of the fungal communities between the continuous cropping and rotation cropping of soybean, maize and wheat. There were 11 potential pathogen and 11 potential biocontrol fungi identified, and the relative abundance of most of the potential pathogenic fungi increased during the long-term continuous cropping of all three crops. The relative abundance of most biocontrol fungi increased in long-term continuous soybean cropping but decreased in long-term continuous maize and wheat cropping. Our results indicate that the response of the soil fungal community structure to long-term continuous cropping varies based upon crop types.